Unified nonlinear analysis of reinforced and partially or fully prestressed concrete sections - Bautista, Leoncio Quirino (1986)
This paper attempts to predict the inelastic behavior of reinforced or partially or fully prestressed concrete sections. The theoretical basis of the non linear analysis procedure and determination of moments, curvature and deflections are discussed. The computer program generated which could analyze rectangular, I or T section yields the location of neutral axis, Bending moment, curvature, and deflection at different stages of loading. The results of the computer test samples show the influence on the inelastic behavior of concrete sections of major variables such as the reinforcement indices, effective prestress, and stress-strain relationships for concrete and steel. Particular emphasis is put also on the agreement between the ultimate moments obtained using the approximate analysis procedure suggested by the ACI Code and non-linear analysis presented. It is concluded that the total reinforcement index affects greatly the behavior of structural concrete section; that is, as it increases the flexural strength increases but deformation ability drastically decreases. It is also suggested that in cases where seismic loadings are considerable the beams should be under-reinforced and partially pre-stresses in order to have large capacity of flexural members to absorb the energy of impact.
Thesis (M.S.)--University of the Philippines Diliman.
Typescript.
Keywords: Prestressed concrete; Reinforced concrete